Development ff Shoot the Ball After Dribble Practice Towards Soccer School Student Athletes - Sabaruddin Yunis Bangun; Amir Supriadi; Ahmad Tarmizi (Journal Physical Education, Health and Recreation, 2020)
The focus of this research is how the development of the shoot the ball after dribble practice for soccer school student athletes. This study aims to find out how the benefits of the shoot the ball after dribble training model for soccer school student athletes. This research uses research and development methods. The subjects in this study were 10 soccer school student athletes in Medan, namely Sejati Pratama Medan, a small scale test and 20 PPLP student athletes in North Sumatra Province on a large scale test. The technique used for data collection in this study was a questionnaire. The questionnaire was used to find out respondents' opinions on the shoot the ball after dribble training model for soccer school student athletes. Questionnaire is a data collection tool that contains a number of questions or statements that must be answered by research subjects. The data analysis technique used is the data from the results of the questionnaire which are classified into two groups of data, namely quantitative data. Quantitative data through field trials, analyzed with quantitative descriptive analysis. To find out whether the development of the shoot the ball after dribble practice on soccer school student athletes is effective. The development of the shoot the ball after dribble practice model for soccer school student athletes can help coaches during the training process, and can be applied in soccer training student athletes, especially when training soccer shooting skills.